A Study on the Relationship Between Students' Motivation and Their Listening and Reading Comprehension - Muid, Abdul; Mohpul, Purnamawati; Rachmawaty, Noor; Iswari, Weningtyas Parama; Syamdianita, Syamdianita; Susilo, Susilo (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2025)
Effective language learning requires a variety of traits, but three things are absolutely necessary: motivation, listening comprehension, and reading comprehension. This study investigates the complex relationships between the motivation of senior high school students and their comprehension of reading and listening. The goal of the study is to determine whether there is a substantial correlation between students' motivation to read and listen comprehension and their actual reading and comprehension scores. To do this, a quantitative research approach employs surveys and standardized reading and listening comprehension exams. A random selection of fifty senior high school pupils was made from one of Bontang's private schools. Through data analysis using Pearson's correlation coefficient, the direction and strength of the relationship between motivation and listening and reading comprehension were determined. The findings show that while reading comprehension and listening comprehension have a strong link, students' motivation for listening and reading comprehension does not have a significant influence.